Business Model Value Chain: Competitiveness Entrepreneurial Retailing Traditional Second-hand Fashion - Sakti, Trenggono Pujo; Rahardjo, Kusdi; Mawardi, M. Kholid (Wacana Journal of Social and Humanity Studies, 2023)
The research aims to utilize the business model value chain to analyze the competitiveness of entrepreneurial retailing of traditional second-hand fashion that potential strategies in Jember. Design qualitative research method case studies with single-case to in-depth interviews with owner/managers retail. The results showed formulating a business model retailing traditional second-hand fashion provides a new lens for competency area, and behavior focus on goal orientation that correlates to reducing surplus waste products and apparel through resale rather than being allocated to the waste system. Thus, research findings utilize the business model value chain on based-oriented: a) sorting, refurbishing, and cleaning as operations, b) innovative redistribution as outbound logistics, c) word-of-mouth as advertising, and d) fitting room simple as service. Therefore, revelatory of the competitiveness highlights the core competency of retailing traditional second-hand fashion on rethinking reducing post-consumer textile waste and further contributing to learning existing business practices. Keywords: value chain model, competitiveness entrepreneurial, retailing second-hand fashion, sustainability